Pembelajaran Kooperatif Pengisian e-filing Bagi Pelaku UMKM di Kelurahan Cipadu-Ciledug-Tangerang - Trisulo, Trisulo; Indrawati, Iin (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
The Directorate General of Tax (DGT) developed various applications to facilitate taxpayers in carrying out tax obligations through e-filing. There are still many taxpayers who do not understand e-filing so come to the tax office to report the tax return. Yet by utilizing e-filing, time and cost can be more productive. UMKM is a new potential in increasing tax contributions. The government through several regulations is aiming at efforts to increase taxation from the UMKM sector. One of them is the reduction of UMKM tax rates from 1% to 0.5%. The problem of understanding and awareness of taxpayers is the key to the success of these efforts. A special strategy is needed to educate the UMKM community. This is a form of mutual responsibility between the people and the government. Some obstacles in taxation socialization include filling e-filing for tax reporting purposes. Difficulties were found in the field in providing socialization material to UMKMs related to tax obligations. Jigsaw type Cooperative Learning in e-filing filling is an effort to increase the taxation potential of the UMKM sector, as well as evidence of government responsibility in public services.